The establishment and development of wound repair discipline in China - Huang, Yuesheng; Fu, Xiaobing (Frontiers in Surgery, 2022)
With the acceleration of population aging and the changes of disease spectrum, the number of wound patients has increased annually in the past 20 years, which has become a major problem in terms of China's medical and health work. To address this challenge, the National Health Commission of China issued a notice in November 2019, requiring qualified medical and health institutions to establish wound repair departments to strengthen the standardized diagnosis and treatment management of various wound patients. This article introduces the establishment process of the wound repair discipline in China, as well as the practice and experience of building a high-level wound repair department in Chinese hospitals, hoping that it can be used for reference by peers.